Advances in the use of active yeast in raising chickens - Aguirre-Guzmán, Gabriel (2025)
The broiler industry supplies quality protein, which is in constant development. It seeks productive strategies that improve production, health, growth, and survival and reduce the poultry industry's diseases, stress, and long-term environmental impact. Broiler chickens are exposed to numerous microorganisms that alter production, and this is an opportunity for yeasts to promote the growth of organisms, stimulate the immune system, improve health, promote changes in intestinal structure, and inhibit pathogens. This review summarizes the current knowledge and effect of active yeast species on raising chickens, nutrition, immunity, digestibility, changes in intestinal structure, and pathogens on those organisms. Due to their nutritional value, active yeasts are used as natural and alternative ingredients in broiler chickens. They are a source of b-glucans, chitin, nucleic acids, mannan-oligosaccharides, b-carotene, and vitamins. Enzymes they produce improve intestinal maturity and digestion. The immune and antioxidant properties of yeasts play an essential role as probiotics and immunostimulants to enhance the resistance of broilers against common viral and bacterial diseases. Bioactive products generated by active yeasts can improve intestinal microbiota and positively alter the immune response, phagocytosis, encapsulation, etc. Different active yeast species and strains have been used and have generated exciting results. They are popular as beneficial candidates for nutrition by maintaining broiler chickens’ health's and well-being conditions. Future studies must understand the functioning and effect of species and strains on broiler chickens in their different processes, the use of new research tools (proteomics, radioisotopes, real-time molecular biology, etc.) can facilitate these studies.